Mitochondrial and peroxisomal population in post-pharyngeal glands of leaf-cutting ants after lipid supplementation - Vieira, Alexsandro Santana [UNESP]; Bueno, Odair Correa [UNESP] (Elsevier B.V., 2015)
The post-pharyngeal gland (PPG) occurs in ants and some Sphecidae wasps. Among its several roles is the storage of lipids from food. In order to investigate the effect of lipids on the cell, especially on mitochondria and peroxisomes, the present study was aimed at examining the peroxisomal and mitochondrial population in the PPG of Atta sexdens rubropilosa after lipid supplementation by confocal laser scanning microscopy and transmission electron microscopy. Soybean oil provided as lipid supplement was not toxic for A. sexdens rubropilosa workers for the first 48 h and 120 h. However, the ultrastructural cytochemical analysis revealed an accumulation of lipid droplets in the PPGs of ants after lipid supplementation at 48 h and 120 h, and smaller lipid droplets in the basal membrane of the PPG epithelium, showing lipid mobilization from the PPG to the hemolymph. The lipid supplementation reduces the life expectancy of medium workers, probably due to the high lipid metabolism. Most importantly, the PPGs of medium workers of leaf-cutting A. sexdens rubropilosa is probably a specialized gland in the lipid metabolism, due to the increased mitochondrial and peroxisomal population inside cells after lipid supplementation; participation of peroxisomal population in the beta-oxidation of long chain fatty acids into smaller chains and participation of mitochondrial population in the beta-oxidation of fatty acids for energy, or mobilization of lipid derivatives from the PPG to hemolymph, a process that requires energy. However, the hypothesis that the PPGs convert lipids from food in aldehydes and/or hydrocarbons must be better investigated. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Leaf-cutting ants; Metabolism; Mitochondria; Peroxisomes; Triacylglycerol